Decision guide on developing livestock enterprises with rural communities in Africa. Part 1: rabbits, goats and poultry - Roothaert, Ralph L. (International Livestock Research Institute, 2005)
The guidelines provided in this document are not intended to be comprehensive, but rather give field workers and researchers an idea of what to think about before planning to develop new livestock enterprises with communities. The aim is to give the reader enough information to be aware of the possibilities, and to provide warnings to prevent situations of classical mistakes resulting in unnecessary failure of the enterprise. The information is complied for the African context. There is a reference list at the end that provides practical and comprehensive background information on tropical livestock rearing.